Nonlinear dynamics. proceedings of the 33rd IMAC, a Conference and Exposition on Structural Dynamics, 2015 /: proceedings of the 33rd IMAC, a Conference and Exposition on Structural Dynamics, 2015. Volume 1 : ([2016]) - Unknown
No abstract available